Evaluation of a stacked‐FET cell for high‐frequency applications (invited paper). (23rd March 2021) - Piacibello, Anna; Costanzo, Ferdinando; Giofré, Rocco; Quaglia, Roberto; Colantonio, Paolo; Pirola, Marco; Camarchia, Vittorio
Abstract: This paper presents the design, electromagnetic simulation strategies and experimental characterisation of a two‐stage stacked‐FET cell in a 100 nm GaN on Si technology around 18.8 GHz, suited for Ka band satellite downlink applications. A good agreement is found between the electromagnetic simulations and the measured performance on the manufactured prototype, thus demonstrating that a successful voltage combining architecture can be obtained in the frequency range of interest with the selected topology, based on a symmetric fork‐like connection between the transistors. This proves the effectiveness of an appropriate electromagnetic simulation set‐up in correctly predicting the crosstalk, which typically affects this structure, leading to a correct stacking operation.